Vpliv serijskega mavčenja na integriteto kože - Ovca, Andreja (Rehabilitacija (Ljubljana), 2014)
Background: Limited mobility of the ankle joint is the most frequent reason for serial casting. The main objective was to identify the factors that negatively influence the integrity of the skin. Methods: We included children referred to the University Rehabilitation Institute in Ljubljana for serial casting program because of decreased ankle range of motion. Data were obtained from personal notes during casting in the years 2010 to 2013. We analysed the number of children, duration of cast applications and the number of skin complications. Results: The data indicate that that duration and multiple casts have got no influence on the integrity of the skin. It appears that the skin reacts individually to the tight and long-lasting contact with the applied materials. Conclusions: Intact skin is necessary to proceed with serial casting. The right choice of materials and education of children and their parents are required to avoid complications.
Keywords: Child; complications; integriteta kože; otroci; serial casting; serijsko mavčenje; skin integrity; zapleti